Manual de la Ley de Propiedad y Cercado de Florida: Posesión Adversa: FE691/FE691, 7/2007 - Olexa, Michael T.; Cossey, Joshua A. (EDIS, 2007)
Spanish version of the "Florida Fence and Property Law" handbook by Michael T. Olexa and Joshua A. Cossey. Published July 2007.